Spin correlations in (Mn,Fe)2(P,Si) magnetocaloric compounds above Curie temperature - Miao, X.F. (ĐHQGHN, 2017)
The longitudinal-field muon-spin relaxation (LF-mSR) technique was employed to study the spin corre-lations in (Mn,Fe)2(P,Si) compounds above the ferromagnetic transition temperature (TC). The (Mn,Fe)2(P,Si) compound under study is found to show itinerant magnetism. The standard deviation of the magnetic field distribution of electronic origin increases with a decrease in temperature, which is attributed to the development of spin correlations. The anomalously low magnetic fluctuation rate is suggested to be another signature of the spin correlations. The development of pronounced magnetic fluctuations is in agreement with the observed deviation of the paramagnetic susceptibility from Curie -Weiss behavior. Our study sheds light on the magneto-elastic transition and the mixed magnetism in (Mn,Fe)2(P,Si) compounds